The Implementation of “wordwall” web-based games as instructional media to improve Arabic vocabulary mastery of 8th grade students at SMP Nurul Huda Modung - Fera Andriani Djakfar Musthafa; Hoirul Anam (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
In digital era, learning is not enough just to be carried out with conventional media. Today's students are close to various applications and websites, so it is necessary to apply them in the learning process. One of the innovative instructional media today is an educational web-based game named “Wordwall”. This application is a learning web-based game in which there are many types of games that students can play. This study aims to find out how to learn Arabic vocabulary using the web-based game